Community-based tourism potential in south Tangerang village - Rudy Pramono; Nova Bernedeta Sitorus; Juliana Juliana; Ira Hubner (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The development of community-based tourism has become an important issue in line with efforts to realize sustainable tourism. Keranggan Villa, a tourist village among 300 villages nominated for the 2021 Indonesian Tourism Village Award, is the only tourist village in the South Tangerang area. This village has various potential attractions, facilities, and communities that support active development. This village has applied the principle of community-based development, but it can still be improved with a better strategic approach. Using a qualitative method, this study aims to describe the community-based tourism development strategy in Keranggan Village. The data used in this study consisted of primary data and secondary data. The primary data sources came from interviews with the Keranggan Village authority, Pokdarwis representatives, and the local communities. Direct observations were also made to KampungKeranggan to learn about the activities and tourism products in KampungKeranggan. Based on the community's involvement in managing the tourism village, KampungKeranggan has the potential for community-based tourism. The development strategy can optimize the empowerment of community potential, the synergy between stakeholders, and integrated marketing support with other tourist destinations around the region.